Risk premia in general equilibrium - Olaf Posch (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper shows that non-linearities imposed by a neoclassical production function alone can generate time-varying and asymmetric risk premia over the business cycle. These (empirical) key features become relevant, and asset market implications improve substantially when we allow for non-normalities in the form of rare disasters. We employ analytical solutions of dynamic stochastic general equilibrium models, including a novel solution with endogenous labor supply, to obtain closed-form expressions for the risk premium in production economies. In contrast to endowment economies, the curvature of the policy functions affects the risk premium through controlling the individual's effective risk aversion.
Keywords: E21; G12; 330; risk premium; continuous-time DSGE; Risikoprämie; Dynamisches Gleichgewicht; Theorie